2009
DOI: 10.3802/jgo.2009.20.2.113
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL-induced cell death and caspase-8 activation are inhibited by cisplatin but not carboplatin

Abstract: Objective: Platinum (Pt) based drugs including cisplatin and carboplatin are widely used as anticancer drugs in various human cancers. Many studies have shown that chemotherapeutic agents synergistically enhance cell death induced by death ligands. However it has been recently reported that cisplatin may inhibit tumor necrosis factorrelated apoptosis-inducing ligand (TRAIL)-induced cell death through inactivation of caspases. Thus, we investigated whether carboplatin also inhibits TRAIL-induced cell death. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…Contradictory studies demonstrating a cisplatin-mediated inhibition of TRAIL-induced cell death through direct inactivation of caspases have also been reported. The authors explain the discrepancy in their results compared to the majority of literature by the dependance on the duration of the treatment [49,50]. In our study, cisplatin was responsible for significant potentiation of TRAIL-induced apoptosis in human prostate and colon cancer cell lines.…”
Section: La-12 or Cisplatin-mediated Increase Of Dr5 Is Essential For Potentiation Of Trail-induced Caspase-8 Activation And Apoptosis Incontrasting
confidence: 54%
“…Contradictory studies demonstrating a cisplatin-mediated inhibition of TRAIL-induced cell death through direct inactivation of caspases have also been reported. The authors explain the discrepancy in their results compared to the majority of literature by the dependance on the duration of the treatment [49,50]. In our study, cisplatin was responsible for significant potentiation of TRAIL-induced apoptosis in human prostate and colon cancer cell lines.…”
Section: La-12 or Cisplatin-mediated Increase Of Dr5 Is Essential For Potentiation Of Trail-induced Caspase-8 Activation And Apoptosis Incontrasting
confidence: 54%
“…Caspase-9 activity was detected after 3 h followed that by caspase-3 activity at 12 h, implying activation of caspase-9 prior to caspase-3. This activity profile was found similar to carboplatin response [ 21 , 22 ]. The aforementioned findings indicate that both the lectins, Bh L and Di L9 induced caspase-dependent apoptosis in a similar manner where caspase-9 is strongly activated.…”
Section: Resultsmentioning
confidence: 52%
“…It has been observed that soluble TRAIL mostly causes apoptosis in tumor cells but not in normal tissues (19). In previous reports, the application of a combined medication for tumor cells with TRAIL and drugs has been evaluated for whether TRAIL could synergize with chemotherapeutic drugs (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%